(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Study Design Case Report.Background and Purpose Myofascial trigger points (MFTP) are the first choice of treatment for all researchers and clinicians in neuromusculoskeletal pain. Trigger point dry needling (TPDN) is an invasive technique involving MFTP stimulation by monofilament needle. The aim of this case study is to find out results of TPDN is main choice of treatment in plantar fasciitis pain patient.Case Description A 32-year-old male patient working as senior cook is suffering from heel pain since 6 month due to long-term standing and wearing tight shoes. Traditionalist administration alternatives for this condition are numerous however there is no solid proof supporting viability of any single choice.This case report concentrated on proof based physiotherapy treatment of a patient with plantar fasciitis. Visual Analog Scale (VAS) score (where 0 shows no torment and 10 greatest conceivable agony) was 510 preceding mediation.The patient was treated for Plantar fasciitis with TPDN and stretching of the plantar fascia and Achilles tendon, intrinsic foot muscle strengthening, manual therapy of myofascial chains and utilize of heel pads. Home activities included myofascial discharge with tennis ball and tin, standing stretches to triceps surae and reinforcing of inborn foot muscles on towel.3 sessions with 3 days interval.Outcomes There was no torment (010) provided details regarding VAS Scale after mediation and no hindrance or utilitarian restrictions, including typical scope of motion.Discussion The patient had the option to return to work with no issue and he had the option to continue his past duties without torment. TPDN with Stretching exercises intervention proved beneficial for the healing of plantar fasciitis. Further future research is recommended to know if TPDN intervention, with stretching exercises is effective in other body parts pain and long-term treatment follow ups in superior patient cluster.